1980
DOI: 10.1002/1097-0142(19801015)46:8<1896::aid-cncr2820460833>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuroblastoma: Influence of age at diagnosis, stage, tumor site, and sex on prognosis

Abstract: A study of a consecutive series of 99 children with neuroblastoma seen at two major Toronto hospitals between 1951 and 1971 is reported. The children who were aged 24 months or less at diagnosis showed an overall two-year survival rate of 59 percent. Analysis, including fitting of a log-linear model, showed that increased probability of survival was associated with younger age at onset, nonadrenal site, and lower staging and the each of these factors acted independently. The sex of the child had no prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
41
3

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(45 citation statements)
references
References 8 publications
1
41
3
Order By: Relevance
“…It is well established that NB of any stage diagnosed in infants have a better prognosis than those diagnosed in children at the same stage [17,19,25,29]. In fact, the main NB prognostic categorization schemes based on morphological parameters were age-linked systems [32,48,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that NB of any stage diagnosed in infants have a better prognosis than those diagnosed in children at the same stage [17,19,25,29]. In fact, the main NB prognostic categorization schemes based on morphological parameters were age-linked systems [32,48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor stage is also an independent prognostic factor in NB: localized tumors have longer survival rates than disseminated ones [17,19]. In the multivariate analysis, we found that INSS stage 4 was the parameter with a more negative effect on hazard rate.…”
Section: Discussionmentioning
confidence: 99%
“…HE PROGNOSIS OF CHILDREN WITH TUMORS Of the T sympathetic nervous system has been shown to correlate highly with several clinical, biochemical, and histologic Shimada et al have recently shown that three morphologic features are particularly useful in predicting the behavior of these tumors: (1) the proportion of neuroblastic and Schwann's cells; (2) the extent of ganglion cell differentiation; and (3) the percentage of mitotic figures and karyorrhectic nuclei (mitotic karyorrhectic index, MKI). Flow cytometric DNA analysis (FCDA), like the MKI, provides information concerning growth lunetics.…”
mentioning
confidence: 99%
“…Finally, we should explain the negative results of classical prognostic indicators such as age, [1][2][3][4] histological category or INPC Prognostic Group 5,6 in our series. Based on the literature and the recent published article by Sano and colleagues, 31 the International neuroblastoma pathology classification adds independent prognostic information beyond the prognostic contribution of age.…”
Section: Discussionmentioning
confidence: 99%